Technological and Organizational Indicators of Customer Relationship Management (CRM): Relationship between Developer Firm, Client Firm and Academic Theory (Perspectivas em Ciência da Informação, 2008)
Customer Relationship Management (CRM) constitutes an instrument that makes possible to identify and to assist the customers' needs. This article verifies the technological and organizacional dimensions of CRM. The study involves a company that builds CRM (HP) and a user firm (Rede Globo). The results indicate that all the variables of the proposed dimensions showed pertinence to the developed study, except the call center system, that inexist in this case. The adopted methodology was the case study with data triangulation.